PRESENCE OF CANDIDA SPP. IN THE SALIVA OF PATIENTS WITH COMPLETE DENTURES, LINED WITH SILICONE-BASED ELASTIC MATERIALS - Mariana Yankova; Bozhidar Yordanov; Radoslav Baykuchev; Vessela Raykova; Ivan Mitov (Peytchinski Publishing, 2017)
Introduction: Patients with advanced bone resorption, non-resilient mucosa or presence of exostoses, require specific methods of prosthetic treatment with complete or partial dentures, namely the use of soft materials for lining. Their porous structure is a prerequisite for bacterial and fungal colonization, that creates conditions for the occurrence of denture stomatitis. The purpose of the present in vivo study is to explore the species and quantity of Candida spp. in the saliva of patients with complete dentures lined with two types of silicone-based elastic materials after a six-month period of observation. Material and methods: The research was conducted upon 45 completely edentulous patients at the age from 48 to 90 (67,9 ± 9,99 years on the average). They were divided into three groups (A, B, C). For the identification and quantity assessment of the presence of Candida spp. in saliva, the researchers used Chrom agar Candida (BioMerieux) and MALDI TOF spectrophotometric analysis - VITEK MS (BioMerieux). Results: The screening of the patients before denture delivery demonstrated absence of Candida spp. in the saliva of 44.4% and Candida albicans - 24.4%. After denture delivery, on the third and the sixth month, we found an increased quantity of C.tropicalis in the patients of groups A and B. In the saliva of the patients with denture stomatitis, the predominantly present species was C.tropicalis (54%) isolated in quantities over 104 CFU/ml. Conclusion: The presence of C. tropicalis in the saliva related to this type of treatment is a prerequisite for the development of hard-to-treat candidoses.